BOOK REVIEW - Cock, I.E. (Pharmacognosy Communications)
In 2012 and early 2013, I undertook a sabbatical project in Johannesburg, South Africa, examining the therapeutic properties of several traditional medicinal plants. At the outset of this project, I was fortunate to meet Professor BenErik van Wyk, one of the authors of this extremely useful volume. As I am not from the Southern African region, my knowledge of the local flora was limited and my discussions with Professor van Wyk provided me with a wealth of information and helped solidify several research project ideas in my mind and guide my selection of species to study. Like the co-author Professor van Wyk himself, the book “Medicinal Plants of South Africa” is an invaluable resource for anyone with an interest in the medicinal plants of this biodiverse region. The book contains detailed descriptions of 150 medicinal plants (with further discussions of closely related species). Individual sections provide a brief overview of the botany, plant part used, medicinal uses, preparation and dosages, active components (where known) and pharmacological effects of the featured species. Each section includes a botanical distribution map as well as chemical structures of the main components and the known (or suspected) bioactive compounds. The authors also include the common names used by the main ethnic groupings that utilise these medicinal plants, allowing for cross-referencing with other ethnobotanical literature. Furthermore, this edition has been updated, including the latest research into each species discussed.